The Influence of the Child Criminal Justice System in the Implementation of Criminal Sansction For Undereges Who Permit Criminal act - Dea Delyana; Selly Ridha Putri; Zhafirah Dinda Lolita; Asmak Ul Hosnah (Universitas PGRI Madiun, 2023)
The application of criminal sanctions against minors has many challenges and obstacles, including in terms of measuring children's guilt, determining appropriate sanctions, and reintegrating children after serving criminal sanctions. The imposition of criminal sanctions against minors can have significant social and psychological consequences, both for the child and the community where the child lives. This paper is prepared based on normative research with analytical descriptive nature. It is stated that Juvenile Justice, in accordance with Law No. 11/2012, is separate from the criminal provisions listed in Article 10 of the Criminal Code and determines sanctions independently. This paper aims for the government to immediately complete the unfinished regulations and prioritize attention to the institutions responsible for the detention and arrest of children and ensure that they are spread throughout Indonesia.